Estuary - Froneman, William (IntechOpen, 2018)
Estuaries are regarded among the most ecologically threatened ecosystems worldwide largely due to poor land use practices within their catchment areas, freshwater abstraction, coastal development, and resource exploitation. Moreover, these systems act as repositories for various anthropogenic contaminants. The establishment and successful implementation of conservation and management strategies are critically dependent on understanding the links among physicochemical, hydrological, and biological variables within these systems. The book provides a comprehensive overview of selected topics including modeling of water exchange between estuaries and the ocean, sediment geochemistry and mangrove health, climate variability and hydrology, and pesticides in estuaries and ecosystem functioning for various estuaries including permanently open, mangrove, and intermittently open/closed systems in both the northern and the southern hemispheres.